2021
DOI: 10.3329/jbcps.v39i2.52390
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal Outcome of Pregnancy with COVID-19: An Observational Study in A Tertiary Care Hospital of Bangladesh

Abstract: Introduction: Corona virus is a new pathogen of high contagious abilities. Pregnant women are at an increased risk due to physiologic changes in their immune, cardiopulmonary and coagulation systems. This study was designed to evaluate the fetomaternal outcome of the pregnant patients with COVID-19. Methods: This retrospective observational study was conducted in CMH Dhaka from May 2020 to July 2020. Total 81 hospitalized pregnant patients with confirmed COVID-19 were enrolled. Relevant data were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In another study, the mean age was 27 which was quite similar to this study. 12 In this study, 51.85% of pregnant women were infected with SARS COV-2 in 3 rd trimester, 35.18% were in 2 nd trimester and 12.96% were in 1 st trimester. Similarly, of the 23 pregnant patients, 19 were in their third trimester of pregnancy and were infected with COVID-19 in another study.…”
Section: Discussionmentioning
confidence: 53%
“…In another study, the mean age was 27 which was quite similar to this study. 12 In this study, 51.85% of pregnant women were infected with SARS COV-2 in 3 rd trimester, 35.18% were in 2 nd trimester and 12.96% were in 1 st trimester. Similarly, of the 23 pregnant patients, 19 were in their third trimester of pregnancy and were infected with COVID-19 in another study.…”
Section: Discussionmentioning
confidence: 53%
“…Ali et al [29] observed that pulmonary oedaema and wound infection rate was apparently higher in cesarean section group than the patents delivered vaginally. A study carried out in Bangladesh also shows higher percentage of pulmonary oedaema (28%) and CVA (10%) in vaginal delivery group [31] . Munro et al [32] reported that acute pulmonary oedema developed more in postoperative period than in postnatal periods.…”
Section: Discussionmentioning
confidence: 85%
“…Although others were seen to have developed slight complications, as COVID-19 during pregnancy was associated with adverse fetal and maternal outcomes. 24,25…”
Section: Resultsmentioning
confidence: 99%